2017
DOI: 10.1016/j.ecolecon.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Financial Performance of Fossil Fuel Firms: A Closer Inspection of their Interaction

Abstract: We investigate the relationship between environmental and financial performance of fossil fuel firms.To this extent, we analyze a large international sample of firms in chemicals, oil, gas, and coal with respect to several environmental indicators in relation to financial performance for the period [2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013]. We find that these firms have significantly higher scores on environmental performance efforts than other firms. We use a simultaneous equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 33 publications
5
73
1
1
Order By: Relevance
“…Damert et al [14] surveyed the factors and long-run performance results of company carbon policy within 45 leading enterprises from the steel, cement, and automotive sector in 2008 and 2013; findings showed that activities to minimise carbon emissions had no association with long-term improvements in carbon performance, despite their relationship to long-term financial returns. Gonenc and Scholtens [15] argued that, for fossil fuel companies (chemicals, oil, gas, and coal), environmental outperformance (over the studied period, 2002-2013) does not influence chemical firm financial performance, diminishes both returns and risks for coal companies, produces mixed effects in oil and gas financial returns, and minimises financial risks in gas and oil companies. Misani and Pogutz [41] used a non-linear approach to investigate environmental results and procedures on corporate financial performance using carbon-intensive firms (from the CDP from 2007 to 2013); they concluded that companies acquired their highest financial returns when their carbon performance was intermediate, that is, neither high nor low.…”
Section: Empirical Study Results and The Development Of The Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Damert et al [14] surveyed the factors and long-run performance results of company carbon policy within 45 leading enterprises from the steel, cement, and automotive sector in 2008 and 2013; findings showed that activities to minimise carbon emissions had no association with long-term improvements in carbon performance, despite their relationship to long-term financial returns. Gonenc and Scholtens [15] argued that, for fossil fuel companies (chemicals, oil, gas, and coal), environmental outperformance (over the studied period, 2002-2013) does not influence chemical firm financial performance, diminishes both returns and risks for coal companies, produces mixed effects in oil and gas financial returns, and minimises financial risks in gas and oil companies. Misani and Pogutz [41] used a non-linear approach to investigate environmental results and procedures on corporate financial performance using carbon-intensive firms (from the CDP from 2007 to 2013); they concluded that companies acquired their highest financial returns when their carbon performance was intermediate, that is, neither high nor low.…”
Section: Empirical Study Results and The Development Of The Hypothesismentioning
confidence: 99%
“…Although, according to Institutional theory, an apparent motive would be to establish stability along with order, the management teams of companies inevitably subscribe to not only consensus and conformity but they also engage with matters of conflict and transformation in social frameworks [13]. Organisational forces are seen as a regulatory body on the interests, goals, and desires of an individual, thereby shaping scenarios for action; such forces may also influence a specific course of action, resulting in continual adoption or transformation [14][15][16]. In this vein, a vital constituent of the social environment affects how institutions are organized, in which organisations have "regulative, normative, and cognitive structures and activities that provide stability and meaning for social behavior" [17].…”
Section: Institutional Theorymentioning
confidence: 99%
“…Based on the work done by CSR researchers, one promising field of enquiry is the study of potential links between social or environmental performance and financial performance of a new venture, which in the corporate realm is frequently shown to be positive (Forcadell & Aracil, 2017;Gonenc & Scholtens, 2017;Heras-Saizarbitoria et al, 2011;Jackson et al, 2015;Li et al, 2017;Muhammad et al, 2015;Wang & Berens, 2015;Wang & Choi, 2013).…”
Section: Financial Performance/csp Indexmentioning
confidence: 99%
“…Modern economies are driven by the availability of reliable energy sources. Conventional energy sources such as fossil fuels (coal, gas, and oil) are being depleted at a fast rate, accompanied by the destruction of ecosystems and habitats, the extinction of wildlife, and pollution of the environment [4][5][6][7][8]. A primary concern of harvesting energy from fossil fuels is that it is unsustainable in the long term, so this has driven researchers and the industry to adopt sustainable and renewable energy technologies.…”
Section: Introductionmentioning
confidence: 99%